THE ROLE OF THIN FUNCTIONAL LAYERS IN SOLID OXIDE FUEL CELLS. (20th June 2016) - Molin, Sebastian; Chrzan, Aleksander; Karczewski, Jakub; Szymczewska, Dagmara; Jasinski, Piotr
Abstract: Widespread commercialization of solid oxide fuel cells requires lowering its cost. It is generally accepted that to lower the cost of solid oxide fuel cells it is necessary to use metal alloys as interconnectors and, consequently, lower its operating temperature to slow down interconnectors degradation. As a result the area specific resistance of the cathodes should be lowered to sustain the performance of the cells. In order to slow the interconnectors degradation (due to corrosion and interdiffusion with the anode) and improve the performance of the cathodes, novel functional layers are introduced to the structure of the fuel cells. In this paper, results related to three kinds of functional layers will be presented: a thin cathode layer between the porous cathode layer and the electrolyte to improve the cathode performance, a buffer layer between the electrolyte and the cathode to slow down inter-diffusion of atoms and thin and dense interconnector coatings to slow down interconnectors degradation. The investigated layers are deposited by cost effective spin coating and spray pyrolysis methods. Introduction of the layers show positive and promising results.